Business Development in Nasarawa State: Effect of Poor Sanitation and Waste Management System - Okon, Emmanuel O. (International Journal of Economics, Business and Management Studies, 2016)
Unimproved sanitation as well as waste management are major barriers to economies worldwide. No towns in Nigeria especially the urban and semi-urban centers of high population density can boast of having found a lasting solution to these challenges, rather the problem continues to assume monstrous dimensions. A field survey was undertaken to examine the effect of poor sanitation and waste management on business development in Nasarawa state, Nigeria. A simple random sampling technique was adopted to select 420 respondents from four towns: Lafia, Keffi, Maraba/Masaka and Eggon/Akwanga. Tables, graphs, pie chart, and simple percentage were used to ascertain the percentage of the respondents while chi-square tool was used to test the formulated hypothesis. The analysis indicates that15.48% of respondents reported that sanitation and waste control practice is not good in the State and that it has adversely affected their businesses as stated by 55.00% of respondents. This study recommends that polluter pays principle of waste management should be introduced in the State. In the same vein, moderately improved and hygienic latrines should be built by government in both urban and rural areas of Nasarawa state.